2020
DOI: 10.3390/nano10081548
|View full text |Cite
|
Sign up to set email alerts
|

Iron Oxide Mediated Photothermal Therapy in the Second Biological Window: A Comparative Study between Magnetite/Maghemite Nanospheres and Nanoflowers

Abstract: The photothermal use of iron oxide magnetic nanoparticles (NPs) is becoming more and more popular and documented. Herein, we compared the photothermal (PT) therapy potential versus magnetic hyperthermia (MHT) modality of magnetic nanospheres, largely used in the biomedical field and magnetic multicore nanoflowers known among the best nanoheaters. The NPs were imaged using transmission electron microscopy and their optical properties characterized by UV-Vis-NIR-I-II before oxidation (magnetite) and after oxidat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
83
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 79 publications
(89 citation statements)
references
References 44 publications
6
83
0
Order By: Relevance
“…Nanoparticle enclosures within endosomes do not decrease the nanoparticles' capacity to heat. Importantly, intracellular aggregation showed a small increase of the nanoparticles' photothermal heating [17,27]. Based on these findings, we herein investigated whether well-defined SPION clustering, and encapsulation by a silica shell (Figure 1), might affect the photothermal yield.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Nanoparticle enclosures within endosomes do not decrease the nanoparticles' capacity to heat. Importantly, intracellular aggregation showed a small increase of the nanoparticles' photothermal heating [17,27]. Based on these findings, we herein investigated whether well-defined SPION clustering, and encapsulation by a silica shell (Figure 1), might affect the photothermal yield.…”
Section: Discussionmentioning
confidence: 95%
“…Iron oxides are also safe [21] and biocompatible [22], and they were already used for magnetic hyperthermia in clinical settings [23,24]. While several research groups reported the efficacy of photo-induced heating of iron oxides [19,[25][26][27], little is known about the effect of iron oxide's silica encapsulation and superparamagnetic iron oxide nanoparticles (SPIONs) clustering on the photothermal yield.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, iron oxide nanoparticles exhibit an extended optical absorbance, which decreases from the near UV to the NIR, thanks to the electronic transition between Fe 2+ and Fe 3+ . In fact, recently, iron oxide nanoparticles have been tested for photothermal therapy in vitro and in vivo [ 13 , 14 , 22 , 27 , 28 , 29 , 30 ]. Therefore, they offer great possibilities to be considered for cancer therapy as a drug delivery system, magnetic hyperthermia and photothermal agent.…”
Section: Introductionmentioning
confidence: 99%
“…It is worth noting that this transition is not present in maghemite [21]. The absorption spectrum of IONs shows a dip in the 700-800 nm region, which covers the largest part of the first biological widow, but it increases considerably in the second biological window range [34,35]. Figure 2a presents the magnetization-magnetic field (M-H) plots at 300 K of IONs.…”
Section: Characterization Of Ionsmentioning
confidence: 98%
“…In this way, Yuan et al demonstrated that IONs coated with polyethylene glycol (PEG) presented anti-cancer activity [33]. However, to the best of our knowledge, there are only few studies on the photothermal therapy application of IONs in the second biological window [34,35].…”
Section: Introductionmentioning
confidence: 99%